Perceptions of Senior High School Students on the English Club Speaking Activities - Sari, Renny Kurnia (ELITE JOURNAL, 2024)
Speaking is the exclusively human act on the process of expressing and exchanging ideas, emotions, and information through the use of oral language. Therefore, this research which was designed in a qualitative method using purposive sampling. Found out that senior high students had positive perceptions on the English club speaking activities. First, they argued that the more courageous, interested and confidents to practice speaking with their friends than in regular class. Second, they claimed that English club made them more experiences in speaking English and more knowledge about English skills. Third, their English. Last, they also stated that after joining the English club, they became more confident and accustomed to speak English in front of public as often as possible.